Experiences from Southeast Asia on nursing education, practice, mobility and influencing policy. (12th October 2019) - Kunaviktikul, W.; Turale, S.; Petrini, M.A.; Tungpunkom, P.; Avant, K.C.
Abstract : In this report from the field, we describe the challenges and opportunities for nursing practice and education, and ways to improve nurse mobility across Asia. We also explain the collaboration within the Southeast and East Asian Nursing Education and Research Network to influence policy development and review. The collaborative process was supported by evidence drawn from discussions at Network meetings, and with nursing and other leaders, an examination of literature and policy documents, and member surveys. We reviewed the region's regulatory statutes which all support diversity in the nursing workforce. The Southeast Asian Nursing Education and Research Network was established in 2015 to support policy development around the upgrading of nurse education, clinical competencies and research capacity, in hospital and primary health care; and facilitating the movement of nurses across national boundaries. Most countries have tried to address policy gaps and their efforts to implement changes are seen in policy expansion and development at the national level. We focus on two policies from the Association of Southeast Asian Nations from 2006 and 2012, that cover nurse mobility, information exchange, nurse capacity building and education and mutual professional recognition of nurses' credentials. However, we found significant variances in education, regulatory policies and clinical competencies that have restricted, and continue to restrict policy implementation. Nursing in South‐East Asia has made significant progress in upgrading standards for education by increasing bachelor degree bridging programs, master and doctoral degrees. Participating countries have passed legislation on licensure, competencies and credentialing of internationally qualified nurses wishing to practice in various contexts. However, much work remains to be done. Implications for nursing policy, education and practice: Governing bodies determine entry into practice law which requires dialogue to enhance policies for domestic and international practitioners for mutual exchange and recognition. Nursing practice and education are under government regulatory bodies but require new policies and laws to ensure adequate educational requirements for safe quality practice.